INFORMATION ABOUT ANCIENT CITIES IN THE OHANGARON VALLEY ACCORDING TO WRITTEN SOURCES - Ubaydulla Ismoilov (Scholar Express Journal, 2024)
This article analyzes information about ancient cities in the Ohangaron Valley according to written sources. Based on 10th-century written records, it provides essential information about the cities in the Shosh and Iloq regions, particularly Tunkat, the capital of the Iloq state. New archaeological research presents diverse opinions among scholars regarding the location of Tunkat and the identification of other cities in Iloq. The article introduces new data on the location of Tunkat, the significance of the Suyurlitepa site, and the ancient Jewish community in this area.
Keywords: Ohangaron Valley; Iloq; Shosh; Tunkat